Organizational Activeness and Obedience in Carrying Out Worship Against Social Piety of Students at Rambah Hilir High School, Rokan Hulu Regency - Ardiansyah Lubis (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This research aimed at knowing the effect of organizational activity and obedience in performing worship to student social piety at State Senior High School 2 Rambah Hilir District, Rokan Hulu Regency. It was a field research with quantitative approach. The samples of this research were 172 students at State Senior High School 2 Rambah Hilir District, Rokan Hulu Regency. Questionnaire and documentation techniques were used for collecting the data. Linear and multiple regression techniques were used for analyzing the data. The results of this research showed that there was a significant effect of organizational activity and obedience in performing worship to student social piety at State Senior High School 2 Rambah Hilir District, Rokan Hulu Regency. It was seen from tobservedttable(0.6380.159) with sig. 0.0000.005 (40.7%). There was a significant effect of obedience in performing worship to student social piety that was seen from robserved rtable(0.6430.159) with sig. 0.0000.005 (41.4%). And there was a significant effect of organizational activity and obedience in performing worship simultaneously to student social piety that was seen from observed Ftable (90.3233.05) with contribution of 51.7%. It means that the contribution of the independent variable to the dependent variable was51.7%.